Survey of Trogolaphysa Mills (Collembola, Paronellidae) of the Brazilian Amazon, including five new species and the description of the dorsal chaetotaxy of the first instar - Cipola, Nikolas Gioia; de Morais, José Wellington; Bellini, Bruno Cavalcante (Zootaxa, 2022)
Here we present a survey of the Trogolaphysa fauna of the Brazilian Amazon, including five new species: amazoccidentalensis sp. nov., T. nigrocephala sp. nov., T. nigrolineata sp. nov., T. pseudomaculata sp. nov., and quinquedentomucronata sp. nov. The new species resemble each other in having 3 macrochaetae in the p3 complex (except for T. amazoccidentalensis sp. nov. with 5) on the second thoracic segment, but differ from each other in color pattern, head chaetotaxy, empodial complex morphology, and number of mucronal teeth. In addition to describing the new species, we describe for the first time diagnostic chaetotaxy features on the antennae, femurs I–III and tibiotarsus. We also provide a description of the dorsal chaetotaxy of the first instar of T. nigrolineata sp. nov., including a comparison with T. jataca (Wray) and T. paracarpenteri Soto-Adames. An identification key to the Brazilian species of Trogolaphysa is provided. This is the first record of nominal species of Trogolaphysa for Northern Brazil and now the number of species endemic to Brazil increases from 8 to 13.